Asymmetric impact of coal and gas on carbon dioxide emission in six Asian countries: Using asymmetric and non-linear approach. (20th September 2022) - Ali, Imad; Sun, Huaping; Tariq, Gulzara; Ali, Hashmat; Baz, Khan; Mahmood, Haider; Khan, Imran; Yao, Jingjing
Abstract: The Industrial Revolution began when machines powered by new energy sources replaced humans, and it has since brought about Climate Change, which is now the world's most challenging concern. This article's primary purpose is to investigate the impacts of coal and gas consumption on environmental quality in six Asian countries: China, India, Russia, Pakistan, Iran, and Bangladesh. While these countries' borders are interconnected, each country's economic growth and environmental changes have repercussions for the others. This analysis uses annual time-series data from 1990 to 2017. We employed modern techniques such as Johansen, NARDL, and asymmetric and symmetric Granger causality. For China and Bangladesh, long-term shock values of coal consumption demonstrate a positive co-integration relationship with carbon dioxide emissions. According to the feedback hypothesis, positive shocks between coal consumption and the environment have a Granger cause-effect for Pakistan and Russia, whereas four other countries do not. Due to rising gas use, the carbon dioxide emissions of Bangladesh have increased over time from the view of symmetric causal effect. According to the residual diagnostics checks, the NARDL model is stable, reliable, and credible in its current state. We discovered asymmetric unidirectional causalities in Russia, Pakistan, and Iran of carbon emission impacts on capital. Furthermore, the Environmental Ministries of the six nations should strictly enforce existing environmental standards, encourage a shift from natural gas and coal to clean energy sources such as ethanol, and promote eco-friendly vehicles such as electric cars and motors. Graphical abstract: Image 1 Highlights: The study focuses on the link between coal, gas consumption with carbon dioxide emissions in China, India, Russia, Pakistan, Iran, and Bangladesh. Long-term shock values of coal consumption reveal a positive co-integration relationship with carbon dioxide emissions for China and Bangladesh. The results suggest an asymmetrical relationship between the factors under consideration.